USE OF DIDACTIC GAME OF PHONETIC ORIENTATION IN THE EDUCATIONAL PROCESS - Tkachuk, O.S. (Pedagogy of Higher and Secondary Education, 2010)
The issue which touches upon the problem of the use of the didactic gama of phonetic direction in the educational and instructional process is thrown light upon in the article. The application of various didactic games makes for the formation of the development if children’s linguistic-aural perception, the enrichment and activization of their vocabulary, the mastering of divices and methods of educativnal-gamesome activity .